NIGERIAN MUSLIMS AND THE INTRIGUES OF THE 1999 CONSTITUTION AS AMENDED: AN EXAMINATION OF ITS PRINCIPLES WITHIN THE CONTEXT OF ISLAMIC LAW - Jamiu Muhammad Busari; Kazeem Adekunle Adegoke (Journal of Islamic Studies and Humanities, 2023)
The sovereignty of the Nigerian 1999 Constitution as amended over its citizens which include Muslims and non-Muslims is absolute and binding. In this regard and despite the absolute power ascribed to this Constitution, Nigerian Muslims like other Muslims are also expected to adhere strictly to all Islamic precepts as enjoined in the Qur’ān and Sunnah amidst the imposition of British-inclined legal system on which the 1999 Constitution was codified. Though, the present Constitution was enthroned on the Country’s nascent democracy by a Military Junta, its constitutionality and appropriateness to Nigerian religious and cultural diversities has become a lingering debate for over two decades.  To this end, this paper examines some of the principles of the 1999 Constitution such as Sharī‘ah application and classification in Nigeria and the syndrome of secularism in the context of Islamic law as they affect Nigerian Muslims. It was then revealed that despite the recognition of Sharī‘ah as a source of law by the Constitution, its applicability and enforcement has been demeaned as a mere customary law for decades. The paper then suggested that to overturn this incongruity, Nigerian Muslims should renew their concerted agitations for total application of Sharī‘ah and enforcement of its jurisdictions from lower to apex courts in Nigeria through constitutional review since the current Constitution was not people-centric.